HUBUNGAN ANTARA KEPUASAN KONSUMEN DENGAN LOYALITAS DI MOFFEE COFFEE STORE MANADO (Relationship between Consumer Satisfaction with Loyalty at Moffee Coffee Store Manado) - Apri Christian Muaja; Celsius Talumingan; Gene H. M. Kapantow (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research is to find out how the relationship between customer satisfaction and loyalty at Moffee Coffee Store Manado. This research was conducted from May 2022 to August 2022. The data used in this study are primary data and secondary data. Primary data obtained from direct interviews with consumers using a questionnaire. Secondary data was obtained from Moffee Coffee Store documents. With the number of respondents as many as 81 people. The sampling technique used was accidental sampling. Data analysis used in this research is descriptive analysis and spearman rank correlation analysis. Based on the research results, the level of customer satisfaction at the Moffee Coffee Store is classified as very satisfied with a total score of 1430. Meanwhile, the relationship between customer satisfaction and loyalty at the Moffee Coffee Store has a positive and significant relationship between the variable customer satisfaction (X) and the variable Loyalty (Y). this is evident from the Spearman rank correlation value of 0.666, so it has a strong relationship level, and with a significant level of 0.000 below 0.05%, this means that the increasing customer satisfaction, will increase loyalty at the Moffee Coffee Store.